The city as place: An urban analysis of three Philippine detective fiction books - Felicilda, Johannah Mari B. (Animo Repository, 2022)
Detective fiction is a developing genre in the Philippines. However, an emerging trend is its use as a vehicle for social commentary. In this genre, analyses are often reflected in the way the city is structured and illustrated, as well as how it affects the characters and narrative. In this study, three texts are analyzed to provide an urban analysis of their city-setting. These three texts and the corresponding cities are Quezon City in F.H. Batacan’s Smaller and Smaller Circles, and Maria L.M. Fres-Felix’s Crimetime: Inspector SJ Tuason Case Files, as well as Binondo in Charlson Ong’s Blue Angel, White Shadow. As guided by Lutwack’s concept of Place and Lefebvre’s urban theories (The Urban Revolution and Critique of Everyday Life), the author analyzed how the urban setting influenced the development and conceptualization of the narrative. In understanding the historical and cultural context of the featured cities, it not only served as the narratives framing device but also provided literal and symbolic valuations to the interpretation of the texts. It reveals that crimes are not anomalies that disrupt the city’s peace and order. Rather, crimes and criminality are the status quo. In Philippine detective fiction, the focus is not primarily on the process of detection, rather on the life of the criminal and even their victims. These stories are not simply puzzles to be solved. They are reflections of urban life. Urban life is inherently violent, however, since the urban phenomenon works dialectically, alongside this evil, there is good. A reality that the authors of these novels predict and foresee.